All the little hopes : a novel - Weiss, Leah, 1947- (Sourcebooks Landmark, 2021)
In North Carolina, during World War II, two girls- Lucy Brown and Allie Bert Tucker- decide to solve crimes just like Nancy Drew. Their chance comes when a man goes missing from town. Before they can solve the case, a Nazi prisoner-of-war camp opens, and more men go missing. Together the girls embark on a journey to discover if we ever really know who the enemy is.